An experimental study of the dual modulation of the colchicine-induced rat model of Alzheimer’s disease by superparamagnetic iron oxide nanoparticles (SPIONs) and the soluble product of Dipylidium caninum adult worm - Amal M. Elsharkawy; Faika Hassanein; Samia S. Abouelkheir; Inas M. Masoud; Wael Felefel; Inas E. Darwish (PLoS ONE, 2025)
Alzheimer’s disease, affecting 7.24 million globally, requires combination therapies, including cholinesterase inhibitors and immunotherapy, for optimal management, emphasizing the benefits of these treatments. The current study investigated the potential synergy between superparamagnetic iron oxide nanoparticles (SPIONs) and a soluble product of Dipylidium caninum adult worms to enhance biochemical and cognitive changes in a colchicine-induced rat model of Alzheimer’s disease. The study involved 50 male albino rats randomly assigned into five groups: group I, the negative control; group II, the positive control; group III, the soluble product of D. caninum excretory-secretory product (ESP)-intervened group; group IV, the SPION-intervened group; and group V, the combination of SPIONs and the soluble product of D. caninum adult worm ESP-intervened group. Each group consisted of 10 rats. The study compared the biochemical and cognitive abilities of the three intervention groups to the negative control using the MANOVA test, revealing a significant fit model (p = 0.000) and a large effect size (partial eta squared = 0.750) for the biochemical improvement. The same results were found for all biochemical tests, including amyloid beta (AB1–42), nuclear factor-kappa B (NF-kB), malondialdehyde (MDA), and superoxide dismutase (SOD). The effect sizes were large (0.551, 0.729, 0.674, and 0.445, respectively), and the fit models were significant (P = 0.000). When comparing the experimental groups pairwise, it was clear that group V was the most effective therapy, as it had the smallest mean difference across all biochemical markers when compared to the negative control group. Regarding cognitive changes, both the multivariate test and tests of between-subject effects of all seven cognitive parameters were significant, with P values ≤ 0.05 and a large effect size due to the partial eta squared values above 0.1. However, for the passive avoidance (PA) effect, initial latency and locomotor activity have medium effect sizes with values between 0.01 and 0.1 (0.061 and 0.018, respectively). Pairwise comparisons between intervention and negative control groups revealed that group IV (SPION-intervened) had the smallest values of cognitive parameters, making it the best intervention therapy for cognitive changes. The Log Rank (Mantel-Cox) Kaplan-Meier curve indicated that the least mean timing needed for cognitive changes to normalize was 20 days at a median point of 0.5, with group III (D. caninum ESP-intervened group) having a significantly different Log Rank (Chi-Square = 85.490, P = 0.000).